Cover crops did not improve soil health but hydroclimatology may guide decisions preventing cash crop yield loss - Sanyal, Debankur; Mukherjee, Avik; Rahhal, Amin; Wolthuizen, Johnathon; Karki, David; Clark, Jason D.; Bly, Anthony (Frontiers in Soil Science, 2023)
Cover crop (CC) is an essential tool to improve or maintain soil health, potentially improving cash crop productivity. Several recent reports of cash crop yield reduction following cover cropping necessitated this research to guide efficient CC decisions in the season before corn (Zea mays) or soybean (Glycine max) is to be grown. Therefore, we designed this multi-year, multi-location study to include the farmers who plant CC following the harvest of a small grain crop, majorly wheat (Triticum aestivum) or oats (Avena sativa), and then grow corn or soybean cash crop in the subsequent season. We also selected the farmers who used a fall CC mix that was winter-terminated, to avoid further complexities. The major objective of this study was to document soil health changes and cash crop yields following CC in eight selected locations around SD for three consecutive CC seasons between 2017-20. Experimental plots were laid out at the farmer-cooperators’ CC fields, where no cover (NC) ‘control’ was tested against CC in a randomized complete block design (RCBD). Soil samples were analyzed for soil health indicators (SHIs) like potentially mineralizable nitrogen (PMN), permanganate oxidizable carbon (POXC), soil respiration (SR), soil microbial biomass (SMB), soil nitrate-nitrogen, soil organic matter (SOM), and other basic soil properties (pH, electrical conductivity, etc.); crop and residue biomass were calculated, and cash crop economic yields were measured. No statistically significant (p<0.05) advantage was found for SHIs or cash crop yields under CC plots compared to NC plots as these fields had healthy soils (long-term no-till was practiced, high SOM levels >30 g kg-1). These findings directed us to investigate hydroclimatological parameters and climatological indices such as accumulated precipitation, standardized precipitation index (SPI), and standardized precipitation evapotranspiration index (SPEI) for their impact on CC’s influence on cash crop yields. Our analyses indicated that hydroclimatology, especially SPEI for the month before CC planting can be used as a tool to guide successful CC decisions, reducing the risk of cash crop yield reductions. Further investigations with SPI and SPEI, along with other climatological parameters are needed to explore and design better CC management tools.